Smart Metering System for Water Distribution in Rural Areas - P., Mangaiyarkarasi; S., Priyanga; F.D., Ashlin; A., Saranya; S., Sowmiya (Journal of Ubiquitous Computing and Communication Technologies, 2025)
Water scarcity and inefficient distribution remain major challenges in rural areas due to manual monitoring and uncontrolled consumption. This research proposes a Smart Metering System for Water Distribution in Rural Areas, which integrates IoT-based automation to improve water management. This system features an automated overhead tank management module that monitors water level and controls the pump, ensuring optimal distribution while notifying Public Works Department (PWD) officers. A consumption-based billing mechanism, employing flow sensors, measures individual household usage, and generates accurate bills. The smart solenoid valve control regulates the flow of water to domestic tanks based on real-time levels, preventing waste. In addition, a dashboard for PWD officers provides real-time monitoring of tank level, pump status, and household consumption patterns. The system also incorporates automated notifications to inform household about water usage and billing, while alerting PWD officers about important issues. This approach ensures efficient water distribution, reduces waste, and improves transparency in rural water management.